2018
DOI: 10.1155/2018/2608419
|View full text |Cite
|
Sign up to set email alerts
|

Data Traffic Offload from Mobile to Wi‐Fi Networks: Behavioural Patterns of Smartphone Users

Abstract: This paper presents a model for defining the behavioural patterns of smartphone users when offloading data from mobile to Wi-Fi networks. The model was generated through analysis of individual characteristics of 298 smartphone users, based on data collected via online survey as well as the amount of data offloaded from mobile to Wi-Fi networks as measured by an application integrated into the smartphone. Users were segmented into categories based on data volume offloaded from mobile to Wi-Fi networks, and nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Accordingly, the concept of showrooming has recently been complemented by the emergence of the concept of webrooming, which refers to the phenomenon when consumers search for information online and buy offline. Since the emergence of this concept, web-rooming has become a valuable source of information which allows for the development of These models are based on the results of the analysis obtained from mobile devices (see, e.g., [14,15]).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the concept of showrooming has recently been complemented by the emergence of the concept of webrooming, which refers to the phenomenon when consumers search for information online and buy offline. Since the emergence of this concept, web-rooming has become a valuable source of information which allows for the development of These models are based on the results of the analysis obtained from mobile devices (see, e.g., [14,15]).…”
Section: Introductionmentioning
confidence: 99%
“…After studying these three couplings, the researcher found that continuity of session during a vertical handover is a major cause of concern for network architectures. The researchers in one study, [8], analysed smartphone users' behavioural patterns during the usage of an offloading service. A total of 298 different users offloaded data from their smartphones to WiFi networks, and the correlation between the preferences of users and mobile data volume was studied.…”
Section: Related Workmentioning
confidence: 99%
“…Smart phones have profoundly altered the way that people organize, socialize, work, and entertain themselves. Nowadays smart phones are an essential piece of business equipment for many professional organizations [29]. The number of smart phone users in the world is forecast to reach 4.7 billion by 2019 [28].…”
Section: Introductionmentioning
confidence: 99%